Hungarian Economy at the Turn of the 19thand 20thCenturiesin the Reports of Russian Diplomats (1899–1903). - Krjucskov, Igor Vlagyimirovics (Acta Scientiarum Socialium, 2012)
At the turn of the century the diplomats of the Russian Consulate-General in Budapest, headed by the head of the consulate Duke Aleksandr Nikolayevich Lvov, closely followed the processes going on in the Hungarian economy. They sent regular reports on their experiences to St. Petersburg. In their reports they did not only deal with the economic achievements and problems, but they also strove to reveal the causes underlying them, they analysed the situation of the individual branches of the economy, the government’s economic policies and the influence of the world economic environment on Hungary. They paid particular attention to the difficulties arising in the Hungarian-Austrian economic relationship and the perspectives of economic relations between the Austro-Hungarian Empire and Russia. Although the reports acknowledge the positive achievements in Hungarian economic development in general, they are more concerned with the difficulties.
Keywords: Russian Consulate General in Budapest; Alexandr Lvov; Austro-Hungarian Empire; Hungarian Economy